Omeprazole and Risk of Hypertension: Analysis of Existing Literature and the WHO Global Pharmacovigilance Database - Merhawi Bahta; Natnael Russom; Amon Solomon Ghebrenegus; Yohana Tecleab Okubamichael; Mulugeta Russom (Adis, Springer Healthcare, 2024)
Abstract Introduction The association between omeprazole and hypertension is poorly documented. The summary of product characteristics of omeprazole approved by major regulators did not mention hypertension as an adverse drug event. Triggered by a locally reported case, this study was conducted to assess the possible causal relationship between omeprazole and hypertension. Methods Globally reported cases of hypertension following use of omeprazole submitted to the World Health Organization global database, VigiBase, were retrieved on 5 March 2024 and analyzed descriptively. Besides this, a literature search was made to identify preclinical, clinical, and epidemiological information on the association between omeprazole and hypertension or increased blood pressure using different data sources. Relevant information, gathered from different data sources, was finally systematically organized into an Austin Bradford-Hill causality assessment framework to assess the causal relationship between omeprazole and hypertension. Results VigiBase indicated a total of 1043 cases of hypertension related to omeprazole from 36 different countries. In the global database, a statistical signal was triggered (IC025: 0.12) on association of omeprazole and hypertension. From the 1043 cases, 65.0% and 10.6% were reported as 'serious' and 'fatal', respectively. Hypertension resolved following withdrawal of omeprazole in 85 cases and recurred after re-introduction of the suspect drug in 14 cases. In 225 cases, omeprazole was the only suspected drug, while in 122 cases, omeprazole was the sole drug administered. When only these 122 cases were considered, 29 cases had positive dechallenge, four cases were with positive rechallenge and the median time-to-onset was 2 days. Literature search identified a possible biological mechanism and some experimental evidence that indicates omeprazole could possibly cause hypertension. Conclusion Currently available totality of evidence suggests there is a possible causal relationship between omeprazole and hypertension. Hence, it is recommended to monitor and report any incidence of hypertension related to omeprazole, and further epidemiological studies are recommended to corroborate the suggested causal association.